ISCHEMIC HEART DISEASES INFORMATION ABOUT ANGINA PECTORIS - Nurxonov Jamshid Nuriddin o’g’li (Galaxy International Interdisciplinary Research Journal, 2024)
Acute erosive and ulcerative lesions of the stomach or duodenum belong to a group of various diseases caused by many causes. The most common cause is peptic ulcer disease. Secondary gastroduodenal ulcer, which develops against the background of diseases of the cardiovascular system, is very relevant and one of the problems that has not been studied enough.